[COVID-19 (Coronavirus) in Fiji : archived websites collected by National Library of Australia]. - Internet Archive (Firm) (Canberra : National Library of Australia, 2020)
This collection provides ongoing access to the online information presented about the COVID-19 in Fiji. It preserves internet sites that contain Fijian government COVID-19 media releases (including the COVID-19 Response Budget Estimate 2019-2020) and online news covered from travel, economic and individual experiences related to the pandemic.
Other COVID-19 web-archiving collections of the selected Asia-Pacific countries are available at https://nla.gov.au/nla.cat-vn8314772
Title supplied by cataloguer.
Mode of access: Available online. Address as at 30/6/2020
Web sites selected and archived as a collection on Archive-It
Keywords: Coronaviruses -- Fiji; Fiji -- Social conditions